(untitled) (TAJ: Journal of Teachers Association, 2009)
A cross-sectional study was carried out to determine the birth weight status of the newborn babies born at Dhaka Medical College Hospital as well as to find out the prevalence of low birth weight among them. All the new born babies (202) born at the labour room of Dhaka Medical College Hospital during the specified period were included in the study. Maximum newborn babies (78.71%) had birth weight 2.5Kg or more and 21.29% had low birth weight (<2.5 Kg). It was found that mean weight of newborn babies was 2.73 Kg and standard deviation was ± 0.52 Kg. Among them 93.56% were full term babies. In a developing country like ours, occurrence of low birth weight is still very alarming, although it is preventable. Emphasis on health education to inform all the women during antenatal visit about the consequences of low birth weight and significance of delivering the babies with normal birth weight is recommended. doi: 10.3329/taj.v17i2.3454 TAJ 2004; 17(2): 95-98